The Fiftieth Anniversary of the Scientific Work of Prof. Dr. Jerzy Ranachowski - MALECKI, Ignacy (Archives of Acoustics, 1998)
The 3-rd International Symposium devoted to new trends in the technology and investigation of ceramic materials was held in Białowieża from the 8-th to 10-th of June this year. The participants of this meeting were scientists working in the field of materials technology and acoustics as well as representatives of the ceramic materials industry and electrical power engineering.